A case study on the effective implementation of the reuse and recycling of construction & demolition waste management practices in Malaysia - Umar, U.A. (Ain Shams University, 2021)
This paper presents a case study on the implementation of the construction and demolition waste management practices in the Malaysian construction sector. The scope was limited to the housing and high-rise buildings. Characterization of reuse and recycling potential was done using descriptive statistics. It is estimated that the waste generated by the housing sector is approximately 16 of the gross materials used, which is about 8.8 million tons/year, and 32 of such waste (approximately 2.8 million tons/year) has the potential for reuse and recycling. However, the high-rise building construction generates construction waste in a large quantity of more than 10 million tons/years (about 70 of the building construction waste), which shows a high potential for reusability and recycling. The reasons behind the low recycling potential for the construction and demolition (C&D) waste generates by the housing sector are found that its quality is low and contains some types of contaminants. Â© 2020 THE AUTHORS